Freedom, Determinism and history in Abraham Ibn Daud - Fernández López, José Antonio (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
This article offers an overview of Ibn Daud’s work with the purpose of reflecting the consequences, limitations and inconsistencies of his peculiar philosophical rationalism set on the defense of the Jewish religious tradition. Accepting the general idea that his philosophy and his historiography constitute a unit, both marked by an apologetic purpose, we will analyse the relations between individual freedom, moral praxis and the evolution of history. In Ibn Daud’s work, the inquiry into human freedom and the meaning of history is indiscernible, if one does not heed the role that the author gives to the divine will in the determination of those same ones and to the limits that he, the first of the peripatetic Jews, establishes between the fiducial and the rational.